Didymophyes bayaramae sp.nov., a new septate gregarine (Protozoa: Apicomplexa) from Aphis fabae of Manipur - Loukrakpam Bina Chanu; Indira Yumnam; Naorem Mohilal (International Journal of Insects, 2024)
The protozoa septate gregarines infect the midgut of Aphis fabae and cause severe infection to the intestinal tissues of the host. During a biodiversity survey on the septate gregarines parasite by the Aphud groups, we collected specimens of Aphis fabae from a bean farm in Imphal, Manipur, India. We dissected the host and isolated some protozoan parasites from the host's midgut. We encountered a new species of septate gregarine, Didymophyses jayaraman sp.nov. Its growth in pairs characterizes the protozoa. Its body parts have epimerites in the anterior body, protomerite in the middle body, and a large deutomerite in the posterior body. The protozoa have a total length of 142.8μm in length. Its trophozoite stage is vase-like; epimerite is papilla-like and becomes disc-like, with prominent ridges radiating from the whole mouth to the top of the protomerite. The protomerite is conical, and the deutomerite is more or less spherical, with a nucleus at the posterior portion. The shape of the sporadin is straight with hemispherical or egg-shaped protomerite, broader than long and ovoidal in shape. Protomerite is ellipsoidal to rhomboidal in shape. Gameyocytes are round, and spores are spherical. The species differs from closely related species Didymophyses rigidus in the shapes of protomerites, deutomerites, gametocytes, and spores. It also differs from Didymophyses berhamporensis in the shapes of trophozoites, epimerites, protomerites, deutomerites, sporadins, gametocytes, and spores. The prevalence of the infection was 25 out of 60 (33.3 %). In the present article, we describe the distinctive characteristics of Didymophyes bayaramae sp.nov and its taxonomic position. We are providing photomicrographs of the parasite at different stages.
Keywords: Aphis fabae; Didymophyes bayaramae .sp.nov. and Manipur; Septate gregarine